Effects of starting score-line, game location, and quality of opposition in basketball quarter score - Sampaioa, J.; Lag, C.; Casais, L.; Leite, N. (European Journal of Sport Science, 2010)
In several team sports, the game starting score-line may be understood as a measure of performance accomplishment and hence might have an effect on players' subsequent efforts. The aim of this study was to identify the effect of the starting score-line, game location, and quality of opposition on basketball game quarter final score. The sample comprised 504 game quarters from the Spanish Basketball Professional League and these were classified as balanced (difference in scores equal of 8 points or less, n=194) and unbalanced (difference in scores of more than 8 points, n=310) using k-means cluster procedures. The effects of the predictor variables on game quarter outcome (difference between points scored and points received) in the whole game and in the second, third, and fourth game quarters were analysed using linear regression analysis. The starting game quarter score-line was only significant in unbalanced situations with very similar effects among different game quarters. The greater the difference in accumulated score at the beginning of each quarter, the more points recovered by the teams who were losing. A small effect from the quality of the opponent was found in the second and third quarters, whereas game location only had an effect when analysing the whole game and second quarter using balanced and unbalanced game quarters combined.